Seasonal Variation of Carbon Metabolism in the Cambial Zone of Eucalyptus grandis - Budzinski, Ilara G. F.; Moon, David H.; Lindén, Pernilla; Moritz, Thomas; Labate, Carlos A. (Frontiers in Plant Science, 2016)
Eucalyptus are the most widely hardwood planted in the world. It is one of the successful examples of commercial forestry plantation in Brazil and other tropical and subtropical countries. The tree is valued for its rapid growth, adaptability and wood quality. Wood formation is the result of cumulative annual activity of the vascular cambium. This cambial activity is generally related to the alternation of cold and warm, and/or dry and rainy seasons. Efforts have focused on analysis of cambial zone in response to seasonal variations in trees from temperate zones. However, little is known about the molecular changes triggered by seasonal variations in trees from tropical countries. In this work we attempted to stablish a global view of seasonal alterations in the cambial zone of Eualyptus grandis Hill ex Maiden, emphasizing changes occurring in the carbon metabolism. Using transcripts, proteomics and metabolomics we analyzed the tissues harvested in summer-wet and winter-dry seasons. Based on 2-DE analysis, 71 proteins were differentially expressed. Transcripts for some of these proteins were analyzed and similar expression patterns were observed. We identified 19 metabolites differentially abundant. Our results suggest a differential reconfiguration of carbon partioning in E. grandis cambial zone. During summer, pyruvate is primarily metabolized via ethanolic fermentation, possibly to regenerate NAD+ for glycolytic ATP production and cellular maintenance. However, in winter there seems to be a metabolic change and we found some sugars highly abundant. Our results revels a dynamic change in E. grandis cambial zone due to seasonality and highlight the importance of glycolysis and ethanolic fermentation for energy generation and maintenance in Eucalyptus, a fast growing tree.